The obsidian chamber ebook - Preston, Douglas (Pendergast,, 2016)
After Pendergast is presumed dead from a supernatural encounter, his bodyguard Proctor is the only one who can chase a kidnapper across international waters and into the deadly unknown. A TRAGIC DISAPPEARANCE After a harrowing, otherworldly confrontation on the shores of Exmouth, Massachussetts, Special Agent A.X.L. Pendergast is missing, presumed dead. A SHOCKING RETURN Sick with grief, Pendergast's ward, Constance, retreats to her chambers beneath the family mansion at 891 Riverside Drive—only to be taken captive by a shadowy figure from the past. AN INTERNATIONAL MANHUNT Proctor, Pendergast's longtime bodyguard, springs to action, chasing Constance's kidnapper through cities, across oceans, and into wastelands unknown. BUT IN A WORLD OF BLACK AND WHITE, NOTHING IS AS IT SEEMS And by the time Proctor discovers the truth, a terrifying engine has stirred-and it may already be too late . . .